ERIC NORDEVALL II — A RECONSTRUCTION OF A PADDLE STEAMER, AN INTENSIVE HISTORICAL PROJECT. (November 2014) - Bornmalm, Lennart; Lagerqvist, Bosse
Abstract : This article presents the reconstruction of the paddle steamer Eric Nordevall that took place between 1995 and 2012 in Forsvik, Sweden. The original steamer was built in 1836 and was specifically designed for traffic the Göta Canal, the mid-Swedish waterway inaugurated in 1832 between Lake Vänern and the east coast. The reconstruction project aimed to produce a design as close as possible to the original, thus representing a historical-intensive research project including the revival of craft skills, such as model carpentry and riveting of pressure chambers. The project has also been important for empowering a local — former industrial — community situated in region with depopulation and loss of employment opportunities. In addition, this article describes the original vessel and her context, which provides an example of the British influence in the early 19th-century industrialisation in Sweden.